Marketing Mix 9P Strategy in Sustaining a Souvenir Shop Business: Strategi Marketing Mix 9P dalam Mempertahankan Bisnis Toko Souvenir - Hardiyanti, Tia; Paningrum, Destina; Sutopo, Arya Budi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Culinary tourism plays a crucial role in promoting local culture and supporting the economy in Indonesia. Specific Background: Solo, a city rich in cultural heritage, offers a wide array of traditional souvenirs, making the souvenir business highly competitive. Knowledge Gap: Previous studies mainly focus on the 4P marketing mix, leaving a gap in understanding the broader and more current 9P approach in sustaining small businesses. Aims: This study aims to analyze the implementation of the 9P marketing mix strategy by Toko Oleh-Oleh Era Jaya in Solo in maintaining its business continuity. Results: The findings indicate that all nine elements—Product, Price, Place, Promotion, People, Process, Physical Evidence, Payment, and Packaging—are applied. However, promotion and physical evidence remain under-optimized. Novelty: Unlike earlier research, this study adopts the expanded 9P marketing mix, offering a more comprehensive and adaptive strategy model for small businesses in the digital era. Implications: The study highlights that integrating traditional values with modern marketing strategies enables local souvenir shops to remain competitive and relevant in an evolving marketplace. This research provides valuable insights for other SMEs in similar cultural and economic settings.Highlight : The research analyzes the use of the 9P marketing mix to sustain a local souvenir shop’s business. Promotion and physical evidence are found to need further optimization. The study fills the gap left by prior research that focused only on the 4P approach Keywords : Marketing Strategy, Marketing Mix, Business Existence, Souvenir Shop, Solo